1996
DOI: 10.1111/j.1528-1157.1996.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine EEG and Temporal Lobe Epilepsy: Relation to Long‐Term EEG Monitoring, Quantitative MRI, and Operative Outcome

Abstract: Results of this study modified our approach in patients with TLE. Interictal epileptiform discharges localized to one temporal lobe on serial routine EEGs or during LTM may be adequate to identify the epileptogenic zone in patients with MRI-identified unilateral medial temporal lobe atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
0
6

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 22 publications
(24 reference statements)
7
124
0
6
Order By: Relevance
“…However, routine EEGs and long-term EEG monitoring can be discordant, and in some patients, interictal epileptiform discharges can be seen only during long-term EEG monitoring. 24 Among the 4 groups, men with left HS had the least amount of AI for both FA and MD. The presence of the most extensive FA, but not MD, alteration of WM in men with left HS fails to explain a probable relationship between AI and extension of pathologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, routine EEGs and long-term EEG monitoring can be discordant, and in some patients, interictal epileptiform discharges can be seen only during long-term EEG monitoring. 24 Among the 4 groups, men with left HS had the least amount of AI for both FA and MD. The presence of the most extensive FA, but not MD, alteration of WM in men with left HS fails to explain a probable relationship between AI and extension of pathologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identified clinical and neuroimaging findings that predict good outcome (7)(8)(9)(10)(11)(12) or increased likelihood for surgical failure (7,8,13); however, few observations of the predictive value of preoperative scalp EEG to outcome after temporal lobectomy have been reported ( I 3,14). Bilateral synchronous spikes or sharp waves and extratemporal or bilateral independent temporal interictal epileptiform activities were reported to be highly associated with surgical failure (1 3 ) .…”
mentioning
confidence: 99%
“…A patient with lateralizing ictal and interictal (i.e., concordant) EEG findings was classified as an optimal surgery candidate, whereas the patient with a nonlateralizing or contralatera1 ictal or interictal finding (i.e., discordant) was classified as a suboptimal candidate. Previous studies have suggested that these two groups may have differing base rates of surgery outcome (1 [8][9][10][11][12][13][14][15][16][17][18][19][20]. We recognize that this distinction is crude, and use it only to illustrate the interaction between base rate and predictive utility.…”
Section: Discussionmentioning
confidence: 99%